Effect of substrate roughness and PVD deposition temperatures on hardness and wear performance of AlCrN-coated WC-Co - Ling, C.L. (Elsevier B.V., 2022)
Elevated temperature experienced in the cutting zone is the main issue contributing to severe wear and responsible in reducing the lifespan of cutting tools'. This study aims to improve the performance of the cutting tool by applying AlCrN coating on the WC-Co substrate using physical vapor deposition (PVD). Prior to the coating process, the WC-Co surface was chemically roughened by Murakami's solution, followed by Caro's solution for 10s. The etched substrates were coated with AlCrN at various PVD deposition temperatures. The scanning electron microscopy (SEM) showed the coating thickness increased from 1.24 Î¼m to 2.78 Î¼m. X-ray diffraction (XRD) pattern confirmed that both AlN and CrN phases dominated the coating layer indicated the presence of AlCrN coating. These XRD peaks were broader, indicating a smaller grain size (11.5 nm) produced at higher deposition temperatures. Apart from that, a minute amount of the Cr2N phase is also detected. The average compressive residual stresses ranged from â5.409 GPa to â1.707 GPa attributed to increased coating thickness associated with Cr2N+N2 â CrN phase transformation. There are no cracking and coating delamination observed at this state. The mechanical properties of the coated structure were further evaluated via Vickers microhardness and linear reciprocating tests. The hardness obtained ranged from 600 to 1617 HV0.2. While the coefficient of friction (CoF) measured was 0.21 after 240 m of sliding distance. The calculated wear rate was 2.283Ã10â4 mm3/NÂ·m which exhibited a significant reduction in wear when coated at 450 Â°C compared to 4.550Ã10â4 mm3/NÂ·m at a lower temperature (250 Â°C). Therefore, it can be concluded that the effect of roughened substrate and various PVD deposition temperatures have significantly influenced the coating phase formation, which subsequently effects the hardness and wear performance of AlCrN-coated tungsten carbide. Â© 2022 Elsevier B.V.